Mobile-Assisted English Reading Comprehension of Narrative Texts in Under-Resourced Schools - Ahmad Zaki Munibi; Yunus Sulistyono (Buletin Pengembangan Perangkat Pembelajaran, 2026)
Limited resources in remote-area schools impede the development of English reading skills, particularly narrative text comprehension. Mobile technology, with its flexible access, offers a potential solution. This study aims to explore students' experiences and teachers' perceptions regarding the use of mobile devices for reading English narrative texts in under-resourced schools. Employing an interpretive phenomenological approach, the research investigates the subjective experiences of students and the views of teachers. The findings reveal that students value the accessibility and flexibility of mobile devices, despite facing constraints such as limited internet connectivity and distractions from other applications. Conversely, teachers acknowledge the potential of mobile devices to enrich learning but also identify technical and pedagogical challenges that hinder effective implementation. This study contributes to the Mobile-Assisted Language Learning (MALL) literature by offering a novel perspective on technology utilization in under-equipped schools, while also providing guidance for more inclusive and adaptive educational policies. Furthermore, these findings establish a foundation for further research to explore specific applications and solutions for optimizing language learning technology in resource-limited settings.